Tradisi Mo Learo dalam Pra Pernikahan Pada Masyarakat Kecamatan Sangkub, Kabupaten Bolaang Mongondow Utara Perspektif Hukum Islam - Mokodenseho, Apriyanto; Jaya M., Umar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2017)
This study discusses the existence of Learo tradition in the community of Sangkub Subdistrict, North Bolaang Mongondow District on the Islamic law perspective. This research is a field research using a legal anthropological approach. Data were collected with observations, interviews and documentation which were then analyzed using qualitative descriptive methods. The results showed that: First, learo is the process of brushing teeth which is carried out to the bride by the family of the bridegroom who is carried out at the bride's house, and her existence is still maintained; Second, Islamic law has given manifestation to the joints of Learo itself, the presence of Islamic law as an intermediary in this tradition by occupying the permissible position.